Exogenous Application of RNAi-Inducing Double-Stranded RNA Inhibits Aphid-Mediated Transmission of a Plant Virus - Worrall, Elizabeth A.; Bravo-Cazar, Ana; Nilon, Alexander T.; Fletcher, Stephen J.; Robinson, Karl E.; Carr, John P.; Mitter, Neena (Frontiers in Plant Science, 2019)
Plant viruses are difficult to control and they decrease both the quality and yield of crops, thus threatening global food security. A new approach that uses topical application of double-stranded RNA (dsRNA) to induce antiviral RNA-interference has been shown to be effective at preventing virus infection in a range of plants following mechanical inoculation. In this study, topical application of dsRNA was effective against mechanical inoculation and aphid-mediated inoculation with the potyvirus bean common mosaic virus (BCMV). Topical application of dsRNAs targeting either the coding region of the potyviral nuclear inclusion b (NIb) protein (BCMVNIb-dsRNA) or the coat protein (CP) coding region (BCMVCP-dsRNA) protected Nicotiana benthamiana and cowpea (Vigna unguiculata) plants against mechanical inoculation with BCMV. BCMVCP-dsRNA was selected for subsequent aphid-transmission experiments. BCMVCP-dsRNA was loaded onto layered double hydroxide nanoparticles to form BCMVCP-BioClay which is a more stable formulation for delivering dsRNA than naked dsRNA. BCMVCP-BioClay was shown to be successful in protecting plants against BCMV transmission by the aphid Myzus persicae. Spraying detached N. benthamiana leaves with BCMVCP-BioClay five days prior to exposure to viruliferous aphids protected the leaves from infection by BCMV. Importantly, spraying of intact N. benthamiana and cowpea plants with BCMVCP-BioClay five days prior to exposure to viruliferous aphids protected plants of both species from BCMV infection. This study demonstrates that topical application of dsRNA using BioClay protects plants from aphid-mediated virus transmission, which is an important first step towards developing practical application of this approach in crop protection.